2013
DOI: 10.1371/journal.pone.0059957
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mutation Reveals Influence of Exopolysaccharide on Lactobacillus johnsonii Surface Characteristics

Abstract: As a competitive exclusion agent, Lactobacillus johnsonii FI9785 has been shown to prevent the colonization of selected pathogenic bacteria from the chicken gastrointestinal tract. During growth of the bacterium a rare but consistent emergence of an altered phenotype was noted, generating smooth colonies in contrast to the wild type rough form. A smooth colony variant was isolated and two-dimensional gel analysis of both strains revealed a protein spot with different migration properties in the two phenotypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 47 publications
8
80
0
Order By: Relevance
“…But it can be clearly expected that different levels of EPS production in L. salivarius strains might affect the functional characteristics of these strains during in vivo transit and other properties. The EPS production level of L. salivarius strains was in a similar range with other LAB strains such as L. rhamnosus GG and L. johnsonii FI9785 (Lebeer et al 2007;Horn et al 2013).…”
Section: Quantification Of Eps Productionsupporting
confidence: 56%
See 1 more Smart Citation
“…But it can be clearly expected that different levels of EPS production in L. salivarius strains might affect the functional characteristics of these strains during in vivo transit and other properties. The EPS production level of L. salivarius strains was in a similar range with other LAB strains such as L. rhamnosus GG and L. johnsonii FI9785 (Lebeer et al 2007;Horn et al 2013).…”
Section: Quantification Of Eps Productionsupporting
confidence: 56%
“…LAB can produce both homopolymeric and heteropolymeric EPS containing only one type of sugar subunit and different sugar subunits, respectively, depending on the presence of the genes related with the production of these polymers (Dertli et al 2013). For the homopolymeric type EPS production, a single gene described as gtf/ftf is required (Walter et al 2008), whereas an eps gene cluster is responsible for the heteropolymeric EPS production in which the priming glycosyltransferase gene (p-gtf) initiates the production of the EPS repeating unit (Horn et al 2013). In addition to the cell surface associated functional characteristics of lactobacilli, production of antimicrobial components plays also crucial roles in probiotic action (Stern et al 2006) as well as in food preservation (H-Kittikun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the genes involved in the capsular polysaccharide of Streptococcus pneumoniae have previously been related to different colony morphology, i.e., rough, small, and mucoid (19). Remarkably, it has recently been shown that mutations in epsC, predicted to encode a tyrosine-protein kinase of an EPS gene cluster and involved in the regulation of capsular EPS biosynthesis in Lactobacillus johnsonii, cause increased levels of EPS and the appearance of a smooth colony variant (33). In relation to this, the Balat_1410 product is a hypothetical membraneanchored protein with a predicted large soluble domain, theoretically involved in the chain length determination of the polymer (34) and harboring, in the mucoid strain, a serine to leucine substitution in the putative soluble part of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…Exopolysaccharides (EPS) were isolated from bacterial strain using the method described previously [10] . Briefly identified Streptecoccus thermophilus strain was grown in 500 ml MRS culture, inoculated at 1% (v/v) with an overnight culture then incubated at 37°C for 2 d. The bacterial supernatant was collected after centrifugation at 6.000 × g for 30 min at 4°C and an equal volume of chilled ethanol was added to the supernatant to precipitate bacterial EPS and stored at 4°C overnight.…”
Section: Isolation Of Exopolysaccharidesmentioning
confidence: 99%